Recent advances and new concepts for the synthesis of axially stereoenriched biaryls. (7th June 2015) - Wencel-Delord, J.; Panossian, A.; Leroux, F. R.; Colobert, F.
<x xml:space="preserve">Abstract</x> Over the past decade the field of the synthesis of axially chiral compounds has been rapidly expanding. Not only key advances have been achieved concerning the already established strategies but also new synthetic routes have been devised. This review showcases the recent developments in this domain.